Gene Expression of Adhesion Molecules in Endothelial Cells from Patients with Peripheral Arterial Disease Is Reduced after Surgical Revascularization and Pharmacological Treatment. (27th February 2013) - Marino, Franca; Guasti, Luigina; Tozzi, Matteo; Schembri, Laura; Castiglioni, Luana; Molteni, Elisabetta; Piffaretti, Gabriele; Castelli, Patrizio; Cosentino, Marco
Abstract : Atherosclerosis is an inflammatory disease characterized by immunological activity, in which endothelial dysfunction represents an early event leading to subsequent inflammatory vascular damage. We investigated gene expression of the adhesion molecules (AMs) ICAM-1, VCAM-1, andβ 1-integrin in endothelial cells (ECs) isolated from venous blood (circulating EC, cEC) and purified from femoral plaques (pEC) obtained from 9 patients with peripheral artery disease (PAD) submitted to femoral artery thrombendarterectomy (FEA). In addition, in peripheral blood mononuclear cells (PBMCs) of the same subjects, we investigated gene expression of IFN-γ, IL-4, TGF-β, and IL-10. Patients were longitudinally evaluated 1 month before surgery, when statin treatment was established, at the time of surgery, and after 2 and 5 months. All AM mRNA levels, measured by means of real-time PCR, in cEC diminished during the study, up to 41–50% of initial levels at followup. AM mRNA expression was significantly higher in pEC than in cEC. During the study, in PBMCs, TGF-β and IL-10 mRNA levels remained unchanged while IFN-γ and IL-4 levels increased; however, the ratio IFN-γ /IL-4 showed no significant modification. In PAD patients, FEA and statin treatment induce a profound reduction of AM expression in cEC and affect cytokine mRNA expression in PBMCs.